The impact of foreign mission on Malaysia's export - Rafiq Idris; Rizal Zamani Idris (Penerbit Universiti Malaysia Sabah, 2018)
Malaysia currently maintains diplomatic relations with foreign countries through 105 missions and has established embassy/high commission and consulate offices in 83 countries. Foreign Mission such as having embassy, high commission and consulate offices abroad is believe to play significant role in determining a country’s export. Many past studies have indicated that Foreign Service has positive impact on trade. This paper attempts to assess the effect of having embassy/high commission offices abroad on Malaysia’s export. Gravity model is used to examine the influence of foreign mission on Malaysia’s total export to rest of the world, using data from year 1990 to 2010.